Pengaruh Kualitas Pelayanan dan Antrian Teller Terhadap Kepuasan Nasabah pada Bank BCA Cabang Kembang Jepun Surabaya - Emilia Pranata; Kevin Lau (Jurnal Simki Economic, 2023)
Service is the process of fulfilling needs through the activities of other people, whichare carried out directly or indirectly. Queuing is a common occurrence in everyday life. Waiting at the counter to get tickets and other situations is a common occurrence. Queues are often encountered in everyday life. Someone is required to wait even though waiting is an activity that requires time, especially long and long queues to get service. Every company creates a method so that customers don't have to wait too long. The study of queues is not something new, we often see long queues at banks when customers queue at the teller to make transactions with the teller. Tellers are bank officers who deal directly with customers whose job is to carry out financial transaction services with customers directly (face to face).